Identifying a community capital investment portfolio to sustain a tourism workforce. Issue 12 (2nd December 2022) - Knollenberg, Whitney; Brune, Sara; Harrison, Jane; Savage, Ann E.
Abstract: Members of the tourism workforce are a crucial resource, whose quality and quantity determine the success of tourism businesses and destinations. Yet, they are frequently subjected to social, psychological, and economic stressors which can result in isolation from destination communities or limited interest in participation in the tourism workforce. Both of these outcomes threaten the sustainability of tourism businesses and destinations, but more importantly create a working environment that can be unjust or unsafe for tourism workforce members. This study relies upon the community capitals framework to identify the resources that currently support the tourism workforce in an island community whose economic and social structure is heavily reliant upon tourism. Analysis of data from in-depth interviews and focus groups with thirty-seven tourism stakeholders reveals the social, cultural, human, and natural capital assets used to support a tourism workforce. An "investment portfolio" for these capitals offers development strategies that can be implemented to help sustain the tourism workforce.